DISTRIBUTION DATA FOR THE TRIBES CERATININI AND ALLODAPINI (HYMENOPTERA: APIDAE) WITH A CHECKLIST OF THE SUBFAMILY XYLOCOPINAE OF TURKEY (Acta Entomologica Serbica, 2016)
The present study is based on bee samples collected in various parts of Turkey since the 1970s. Examination of the material and an overview of the literature sources allowed us to reach the conclusion that the genus Ceratina Latreille (Ceratinini) includes 27 species and two subspecies, while only one species of the genus Exoneuridia Cockerell (Allodapini) is found in Turkey. With a current 10 Xylocopa species previously recorded, a total of 38 species and two subspecies in the subfamily Xylocopinae occur in the country. Each species has a different distribution range; some Ceratina species are abundantly or moderately distributed, but certain species are very rare: C. christellae has been known from Antalya and Hakkâri, C. hakkarica from Hakkâri, C. neocallosa from Nevşehir, C. rasmonti from Ağrı and Van, C. warnckei from Hakkâri, Kahramanmaraş and Şırnak, C. schwarziana from Hakkâri and Kars. Ceratina chalcites ebmeri, C. denesi, C. hakkarica, C. rasmonti, C. warnckei and Exoneuridia hakkariensis are Anatolian endemics. Moreover, 12 Ceratina taxa and E. hakkariensis have been described from Turkey, of which six taxa have type localities in Hakkâri (C. hakkarica, C. schwarziana, C. warnckei, C. zwakhalsi, C. chalcites ebmeri and E. hakkariensis). Thus, the eastern part of Turkey, especially Hakkâri, is a very important speciation center for Ceratinini bees. For most of the species, new distribution records are provided, and plant species visited and nesting sites are included. It was first determined that C. bispinosa and E. hakkariensis visited Capsicum annuum L., which is the most common and extensively cultivated vegetable in Turkey. For rare taxa, a distribution map was established. Furthermore, a checklist for the Turkish Xylocopinae is provided for the first time.